Research progress of immune checkpoint inhibitors in the treatment of metastatic colorectal cancer - TU Juanjuan; JIN Zhiming (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Colorectal cancer (CRC) is a common malignancy with a high incidence of metastatic events in China and the world. Immunotherapy has received increasing attention as an emerging therapy in the treatment of metastatic colorectal cancer (mCRC). Immune checkpoint inhibitor (ICI) is one of the important methods, mainly represented by programmed cell death protein 1 (PD-1), programmed cell death ligand 1 (PD-L1) and cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) antibodies. The strong potential of ICIs in the treatment of mCRC has been confirmed by completed and ongoing clinical trials. The U.S. Food and Drug Administration has approved some ICIs for the first-line treatment of microsatellite instability-high (MSI-H)/mismatch repair deficient (dMMR) mCRC. ICI cannot yet replace the conventional therapy in the treatment of microsatellite stable (MSS)/mismatch repair proficient (pMMR) mCRC, but an increasing number of ICI combination programs have entered the clinical trial phase and have initially shown good clinical efficacy and application prospects. Finding new markers to identify potentially beneficial patients, validating new combination regimens, and developing new immune checkpoints are all important to the future of ICI research.